Aerobic vaginitis in the third trimester and its impact on pregnancy outcomes - Anh Thi Chau Nguyen; Na Thi Le Nguyen; Thu Thi Anh Hoang; Tuyen Thi Nguyen; Trang Thi Quynh Tran; Dan Nu Tam Tran; Anh Thi Kim Nguyen; Linh Manh Tran; Duc Huu Chau Nguyen; Tam Minh Le; Binh Duy Ho; Tiiu Rööp; et al. (BMC, 2022)
Abstract Background Aerobic vaginitis (AV) is a vaginal inflammation characterized by disruption of the lactobacillus microbiota and increased counts of different aerobic bacteria. AV may result in severe complications, especially during pregnancy, including preterm delivery, neonatal and maternal infections. This study aimed to determine the prevalence of AV in the third trimester of pregnancy, and the relationship between AV and pregnancy outcomes.  Methods A cross-sectional descriptive study included 323 pregnant women attending for routine antenatal care in the Hue University Hospital. Vaginal samples collected at the third trimester of pregnancy were evaluated for AV according to the scoring system of Donders and cultured for identification of predominant bacteria. Pregnancy was followed to its end, and pregnancy outcomes were recorded for both mothers and infants. Results The proportion of pregnant women diagnosed with AV in the third trimester was found to be 15.5%, with the vast majority of the cases (84%) displaying the light AV and 16% the moderate AV. The vaginal cultures in the women with AV revealed most frequently Streptococcus agalactiae (6%), followed by Enterococcus spp (4%), Staphylococcus aureus (4%), and Acinetobacter baumannii (2%). In addition, AV during the last trimester of pregnancy was associated with an increased risk of puerperal sepsis (OR 8.65, 95% CI: 1.41-53.16, p = 0.020) and there was a slightly increased risk for neonatal infections, which was statistically insignificant. Conclusions The proportion of AV is relatively high in Vietnamese pregnant women. Since it is associated with an increased risk of puerperal sepsis, it needs to be diagnosed and treated before delivery.